209k views
3 votes
Write an equation of a circle with center {-1,2} passing through the point {2,4}

User Peterph
by
5.0k points

2 Answers

3 votes

Answer:

The equation of circle passing through points (2, 4) and center (-1 , 2) is (x + 1 )² + (y - 2)² = 13

Explanation:

Given as :

The circle having center = (-1 , 2)

The circle passes through point = (2, 4)

Now, Standard equation of circle with center and passing through points is

(x - h)² + (y -k)² = r²

where h and k are the center of circle and r is the radius of circle

Now the center as (h,k) = (-1 , 2)

And passing through points (x,y) = (2, 4)

Now, satisfying the center and points on standard circle equation

I.e (x - h)² + (y -k)² = r²

Or, (2 - (-1) )²+ (4 -2)² = r²

or, 3² + 2² = r²

or, r² = 9 + 4

Or , r² = 13

r =
√(13)

Now circle equation

(x - (-1) )² + (y -2)² = (
√(13)

or, (x + 1 )² + (y - 2)² = 13

So, equation of circle is (x + 1 )² + (y - 2)² = 13

Hence The equation of circle passing through points (2, 4) and center (-1 , 2) is (x + 1 )² + (y - 2)² = 13 Answer

User Chchrist
by
5.4k points
3 votes

Answer:

The equation of the circle is given by,


(x-2)^(2) + (y-4)^(2) = (√(13))^(2)

Explanation:

The center of the circle is given as (-1,2) and it passes through (2,4).

The distance between the two points is radius of the circle.


(Distance) = \sqrt{(x2-x1)^(2)+(y2-y1)^(2)}

Radius =
\sqrt{(2-(-1))^(2)+(4-2)^(2)}

Radius =
√(13)

The equation of the circle is given by,


(x-x1)^(2) + (y-y1)^(2) = (Radius)^(2)

Inserting above values,


(x-2)^(2) + (y-4)^(2) = (√(13))^(2)

User Or Duan
by
5.4k points